2021
DOI: 10.1093/ckj/sfab087
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-free regional anticoagulation of haemodialysis filters with calcium-free dialysate: is citrate mandatory?

Abstract: Background There is an unmet need to develop safe and successful heparin-free regional anticoagulation modalities in haemodialysed patients at risk of bleeding. Whether the addition of citrate as a prefilter injection or in the dialysate itself is required to reach anticoagulation objectives when calcium-free dialysate is used as regional anticoagulation remains unclear. Methods In this monocentric retrospective study, we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…They confirmed the efficacy and safety of this feedback over a total of more than 1250 sessions with numerous types of dialyzers (Figure 3). In the study by Medrano et al reporting the largest number of sessions, no patient out of 316 developed symptomatic dyscalcemia during the 908 dialysis sessions lasting between 3.5 and 6 h, 4 and no symptomatic dyscalcemia was reported in any of the other studies. The use of calciumfree dialysate can thus be simplified, as it is no longer necessary to monitor blood calcium levels during dialysis.…”
Section: Adjustment Of Calcium Infusion Rate According To Ionic Dialy...mentioning
confidence: 86%
See 3 more Smart Citations
“…They confirmed the efficacy and safety of this feedback over a total of more than 1250 sessions with numerous types of dialyzers (Figure 3). In the study by Medrano et al reporting the largest number of sessions, no patient out of 316 developed symptomatic dyscalcemia during the 908 dialysis sessions lasting between 3.5 and 6 h, 4 and no symptomatic dyscalcemia was reported in any of the other studies. The use of calciumfree dialysate can thus be simplified, as it is no longer necessary to monitor blood calcium levels during dialysis.…”
Section: Adjustment Of Calcium Infusion Rate According To Ionic Dialy...mentioning
confidence: 86%
“…Since these two studies, several others have confirmed the efficacy of this procedure. They showed a comparable percentage of sessions having to be interrupted prematurely due to filter clotting: 3 out of 101 (3%) 7 by Faguer et al., no sessions out of 44 (0%) by Vigneron et al., 8 20 out of 908 (2.2%) by Medrano et al., 4 3 out of 96 (3.2%) by Faguer et al 9 . In all, only 27 sessions out of 1228 (2.2%) failed.…”
Section: Use Of a Citrate‐containing Dialysatementioning
confidence: 90%
See 2 more Smart Citations
“…Notably, it remains essential to consider the place of vitamin E-coated membranes in the broader context of currently available heparin-free dialysis techniques, such as regional citrate anticoagulation (RCA) and predilution hemodiafiltration. Owing to its safety and efficacy, RCA has been widely adopted in clinical practice for both critically ill and hemodialysis patients at high risk of bleeding and filter clotting [28][29][30]. However, the utilization of RCA is not devoid of challenges.…”
Section: Vitamin E-coated Membranes For Anemia Managementmentioning
confidence: 99%